Causation of Crohn’s Disease by Mycobacterium avium Subspecies Paratuberculosis - John Hermon-Taylor; Timothy John Bull; Joseph Michael Sheridan; Jun Cheng; Michael Laurence Stellakis; Nasira Sumar (Canadian Journal of Gastroenterology)
Mycobacterium avium subspecies paratuberculosis (MAP) is a member of the M avium complex (MAC). It differs genetically from other MAC in having 14 to 18 copies of IS900 and a single cassette of DNA involved in the biosynthesis of surface carbohydrate. Unlike other MAC, MAP is a specific cause of chronic inflammation of the intestine in many animal species, including primates. The disease ranges from pluribacillary to paucimicrobial, with chronic granulomatous inflammation like leprosy in humans. MAP infection can persist for years without causing clinical disease. The herd prevalence of MAP infection in Western Europe and North America is reported in the range 21% to 54%. These subclinically infected animals shed MAP in their milk and onto pastures. MAP is more robust than tuberculosis, and the risk that is conveyed to human populations in retail milk and in domestic water supplies is high. MAP is harboured in the ileocolonic mucosa of a proportion of normal people and can be detected in a high proportion of full thickness samples of inflamed Crohn’s disease gut by improved culture systems and IS900 polymerase chain reaction if the correct methods are used. MAP in Crohn’s disease is present in a protease-resistant nonbacillary form, can evade immune recognition and probably causes an immune dysregulation. As with other MAC, MAP is resistant to most standard antituberculous drugs. Treatment of Crohn’s disease with combinations of drugs more active against MAC such as rifabutin and clarithromycin can bring about a profound improvement and, in a few cases, apparent disease eradication. New drugs as well as effective MAP vaccines for animals and humans are needed. The problems caused by MAP constitute a public health issue of tragic proportions for which a range of remedial measures are urgently needed.